Hepatitis E in a region of Italy: An emerging autochthonous infection?. Issue 11 (November 2016) - Tarantino, Giuseppe; Bagnarelli, Patrizia; Marzioni, Marco; Marinelli, Katia; Surace, Giulia; Traini, Sara; Baroni, Gianluca Svegliati; Menzo, Stefano; Benedetti, Antonio
Abstract: Background: Recent data showed an increasing number of "autochthonous" cases of hepatitis E in Italy. Aims: Analysing cases of acute hepatitis E to define frequency, clinical features, prognosis and risk factors. Methods: We considered all the patients admitted to our Regional Hospital between August 2011 and September 2014, with a diagnosis of acute hepatitis; serological screening for hepatitis B, C and A viruses was performed; in the event of negative results, sera were tested for cytomegalovirus, Epstein–Barr and hepatitis E viruses. Results: Among 200 patients, 66 were affected by viral infection. IgM anti-HEV was detected in 14 patients with a predominance of males (79%) with a mean age of 55. Genotype 3 of HEV was found in 8 patients. Only one patient died of acute on chronic liver failure; all others evolved favourably towards clinical remission within two months from clinical onset. Thirteen patients had had local exposure to infection and 9 reported the consumption of raw or undercooked locally produced pork. Conclusion: The incidence of HEV in our cohort of patients with acute viral hepatitis is high (about 20% per year). In over 85% an autochthonous exposure to infection could be recognised, with a clear link with food habits.